Biopsychosocial correlates of hope in Asian patients with cancer: a systematic review. Issue 10 (6th October 2016) - Mahendran, Rathi; Chua, Shi Min; Lim, Haikel A; Yee, Isaac J; Tan, Joyce Y S; Kua, Ee Heok; Griva, Konstadina
Abstract : Objective: To examine the factors associated with hope and hopelessness in patients with cancer in Asian countries, and the instruments used to measure hope and hopelessness. Methords: A comprehensive systematic review was conducted with search terms, including cancer, hope, hopelessness and individual Asian country names, on CINAHL, Embase, PsycINFO, PubMed and Scopus databases. Only quantitative studies on adult cancer populations in Asia examining hope or hopelessness were included. Results: A total of 2062 unique articles were retrieved from the databases, and 32 studies were selected for inclusion in this review. Hope and hopelessness were most frequently measured with the Herth Hope Index and the Mental Adjustment to Cancer Scale, respectively. The biopsychosocial factors that were most consistently associated with hope and hopelessness included sociodemographic variables (education, employment and economic status); clinical factors (cancer stage, physical condition and symptoms); and psychosocial factors (emotional distress, social support and connections, quality of life, control or self-efficacy, as well as adjustment and resilience). Discussion: There is a need for more studies from South and Southeast Asia as most studies hailed from East Asia. This review highlighted the possibility of cultural differences influencing factors related to hope, suggesting that cross-cultural studies specifically would facilitate understanding behind these variations, although future reviews on hope should also include studies on hopelessness for a comprehensive understanding of the concept. Finally, more longitudinal research could be conducted to assess whether the factors associated with hope and hopelessness change over time and disease progression.